Back Cover: Triggering Gel Formation and Luminescence through Donor–Acceptor Interactions in a C3‐Symmetric Tris(pyrene) System (Chem. Eur. J. 17/2016). Issue 17 (16th March 2016) - Lai, Thanh‐Loan; Pop, Flavia; Melan, Caroline; Canevet, David; Sallé, Marc; Avarvari, Narcis
Abstract : Luminescent supramolecular organogels are attractive soft materials for photonic applications, especially when they contain electroactive units, as the gelating and emission properties can be modulated by the addition of electron‐donor or ‐acceptor counterparts. A C 3 symmetric tris(pyrene) based on a 1, 3, 5‐tris(bipyridylamido)‐benzene central core meets this criteria and exhibits tunable gelating and luminescent behaviour. More information can be found in the Communication by N. Avarvari, D. Canevet et al. onpage 5839 ff.